Analisis Kepemimpinan, Lingkungan Kerja, Dan Budaya Kerja Terhadap Motivasi Kerja Karyawan Kocok In Cafe - Clarisa Maytania (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
The culinary business that is mushrooming at this time makes business owners have to be creative and compete in maintaining their business, one way is by increasing the work motivation of their employees. The purpose of this study is to determine and analyze the influence of leadership, work environment, and work culture on the work motivation of employees of Beat In Cafe. This study uses a quantitative approach and the technique used is causal associative. The population and samples used in the study were all employees of Kocok In Cafe, totaling 35 respondents and analyzed using multiple linear regression methods. The results of this study indicate the influence of leadership, work environment and work culture on the work motivation of employees of Kocok In Cafe.